EMPLOYEE'S PERCEPTION OF THE WORK ENVIRONMENT IN THE PREVENTION EFFORT INFECTION OF COVID-19 - Yudha, Yudha Bhaktiono; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Corona Virus Disease 19/COVID-19 has an impact on utility services. Utility services such as clean water, electricity supply, security, and cleanliness are included in the scope, especially in the town management. This qualitative research with a case study design aims to get an overview of employee perceptions regarding the prevention of COVID-19 transmission. The study was conducted at Kelapa Dua Sub-district, Bencongan Indah Village, Tangerang on 5/five informants who worked in the Town Management. Data were collected through interviews with the implementation of health protocols and analyzed using a problem-solving approach with Fishbone Analysis. The results showed that until June 2022 83 employees were exposed to COVID-19. This is due to several factors, such as human resources, machines, methods, budgets, materials, and the environment, such as the number of operational working hours serving residents/residences for 24 hours, there is no task force team/Satgas COVID-19, there are no tools to check the conditions exposed to workers, there is no SOP/Standard Operating Procedure to implement health protocols, the price of Swab/PCR and mask examinations are expensive, there are no vaccines at the beginning of the pandemic, and health protocols implementation at homes and in public inconsistent. Need more efforts to increase positive perceptions such as the creation of a special team for the COVID-19 Task Force and efforts to increase employee awareness to implement health protocols consistently.